To Touch Time: U.S. Black Feminist Modernist Sculpture in the 1970s and 1980s - Sarah Louise Cowan (Arts, 2024)
Modernist propositions long have been understood as atemporal—somehow outside of time—or insistently hailing the future. This temporal framework suppresses the contributions of those excluded from modernist canons, particularly Black women. In this article, visual and material analysis of sculptural works produced in the 1970s and 1980s by U.S. Black women artists Beverly Buchanan, Senga Nengudi, and Betye Saar reveal how Black feminists have engaged with modernist protocols in order to redress cultural erasures of Black women. These practices exemplify Black feminist modernisms, or creative practices that unsettle the racist and sexist logics of dominant cultural institutions. Each of these artists utilizes haptic surfaces as a method for defying institutional modernism’s obfuscation of the past. The analysis focuses on Buchanan’s defiance of memorial erasures, Nengudi’s reenactment of labor, including in its historical forms, and Saar’s adaptation of generational memory-making processes. Ultimately, these artists’ rejection of a “timeless” modernism demands that viewers understand the present moment in relationship to a still-evolving past. In this way, Buchanan, Nengudi, and Saar position the present as an accumulation, rather than transcendence, of historical occurrences.